2014
DOI: 10.1007/s11552-014-9716-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications of Open Trigger Finger Release

Abstract: Background Open trigger finger release is generally considered a simple low-risk procedure. Reported complication rates vary widely from 1 to 43 %, mostly based on small studies. Our goal was to determine the incidence of complications in a large consecutive series, while also identifying potential risk factors. Methods All open trigger finger releases performed from 2006 to 2009 by four fellowship-trained hand surgeons at a single institution were retrospectively reviewed. There were 795 digits released in 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 11 publications
3
41
1
5
Order By: Relevance
“…9 Retrospective studies in the past few decades have extensively reported postoperative complications after open trigger finger release, such as persistent or recurrent triggering, nerve injury, infection, wound problems, and slow recov-ery of motion requiring hand therapy. 2,4,7,17,19,23 However, only 1 study to date has specifically examined recent steroid injection as a factor associated with complications in open trigger release. In a 2014 retrospective review of many potential risk factors, Everding et al 7 found that age, diabetes, hypothyroidism, recent injection, and concurrent procedures were not associated with a greater incidence of complications (persistent pain, swelling, stiffness, recurrent triggering, infection, neurapraxia, bowstringing) in 795 digits belonging to 543 patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Retrospective studies in the past few decades have extensively reported postoperative complications after open trigger finger release, such as persistent or recurrent triggering, nerve injury, infection, wound problems, and slow recov-ery of motion requiring hand therapy. 2,4,7,17,19,23 However, only 1 study to date has specifically examined recent steroid injection as a factor associated with complications in open trigger release. In a 2014 retrospective review of many potential risk factors, Everding et al 7 found that age, diabetes, hypothyroidism, recent injection, and concurrent procedures were not associated with a greater incidence of complications (persistent pain, swelling, stiffness, recurrent triggering, infection, neurapraxia, bowstringing) in 795 digits belonging to 543 patients.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,7,17,19,23 However, only 1 study to date has specifically examined recent steroid injection as a factor associated with complications in open trigger release. In a 2014 retrospective review of many potential risk factors, Everding et al 7 found that age, diabetes, hypothyroidism, recent injection, and concurrent procedures were not associated with a greater incidence of complications (persistent pain, swelling, stiffness, recurrent triggering, infection, neurapraxia, bowstringing) in 795 digits belonging to 543 patients. However, anecdotal evidence among hand surgeons has continued to question whether or not recent steroid injection may be related to complications following open trigger finger release.…”
Section: Introductionmentioning
confidence: 99%
“…Tetik parmak cerrahisi sonrası komplikasyonlarda risk faktörü olarak; erkek cinsiyet, ameliyatın sedasyon altında ve genel anestezi altında olması kabul edilmektedir (16). Çalışmamızdaki olguların çoğu bayan olup, ameliyat sırasında rejyonel anestezi uygulanması sebebi ile herhangi bir komplikasyon görülmemiştir.…”
Section: Discussionunclassified
“…89 The overall complication rate is 12% in one series of 795 trigger fingers treated surgically, with major complications necessitating return to theatre occurring in 2.4%. 90 Minor issues include scar pain, superficial infection, stiffness (3%), and protracted wound care (2%). 86 Bowstringing from over-release of the pulley system 91 and nerve injuries 86 …”
Section: Open Releasementioning
confidence: 99%